Islamic Religious Education Teachers' Strategies in Improving Learning Outcomes in Students through a Complete Learning Model at SMP Negeri 7 Balaesang Tanjung, Donggala Regency - Halima, Nur (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The purpose of this study was to determine the strategy of Islamic religious education teachers in improving learning outcomes in students through a complete learning model at SMPN 7 Balaesang Tanjung, Donggala Regency. This type of qualitative research or field research, consisting of research location, researcher presence, data and data sources, data collection techniques, data analysis techniques, and data validity checks. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and behaviors that can be observed. so that researchers collect three components, namely data reduction, data presentation and data verification. The results showed that 1). The strategies used by Islamic religious education teachers in improving student learning outcomes are by providing reinforcement, giving grades, holding competitions, giving praise, punishment, creating a pleasant learning atmosphere and holding tests. 2). The obstacles faced in the use of a complete learning model in Islamic religious education subjects are related to the readiness of human resources including; educators, students and parents of students, the absence of an appropriate curriculum according to school conditions, limited time allocations, inadequate media and supporting infrastructure which results in the application of the implementation of complete learning in Islamic religious education subjects not running properly.